2016
DOI: 10.3847/0004-637x/824/1/30
|View full text |Cite
|
Sign up to set email alerts
|

Chang-Es. Vii. Magnetic Outflows From the Virgo Cluster Galaxy NGC 4388

Abstract: We investigate the effects of ram pressure on the ordered magnetic field of a galaxy hosting a radio halo and strong nuclear outflows. New radio images in total and polarized intensity of the edge-on Virgo galaxy NGC 4388 were obtained within the CHANG-ES EVLA project. The unprecedented noise level reached allows us to detect striking new features of the ordered magnetic field. The nuclear outflow extends far into the halo to about 5 kpc from the center and is spatially correlated with the Hα and X-ray emissio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 55 publications
2
41
1
Order By: Relevance
“…Examples are NGC 4388 (e.g. Hummel & Saikia 1991;Damas-Segovia et al 2016, among others) and NGC 3079 (Hummel, Van Gorkom, & Kotanyi 1984, and others) and these are also seen in the panels of Appendix B. Fig.…”
Section: Jets/lobesmentioning
confidence: 87%
“…Examples are NGC 4388 (e.g. Hummel & Saikia 1991;Damas-Segovia et al 2016, among others) and NGC 3079 (Hummel, Van Gorkom, & Kotanyi 1984, and others) and these are also seen in the panels of Appendix B. Fig.…”
Section: Jets/lobesmentioning
confidence: 87%
“…Dust extinction effects decrease with increasing wavelength, and so IR emission should be largely unaffected. The Continuum Halos in Nearby Galaxies -an EVLA Survey (CHANG-ES; Irwin et al 2012aIrwin et al ,b, 2013Wiegert et al 2015;Irwin et al 2015;Li et al 2016;Damas-Segovia et al 2016;Irwin et al 2016) aims to establish the connection between star formation in galaxy disks and non-thermal processes, like halo magnetic fields, CR injection and propagation, and active galactic nuclei (AGN). To accomplish this goal, CHANG-ES has observed 35 highly-inclined galaxies in the nearby universe with the NSF's Karl G. Jansky Very Large Array (VLA) in B, C, and D configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Damas-Segovia et al (2016) reported a southern jet with a scale of 1 kpc. Extended radio emission is observed in our 33 GHz map with a P.A.…”
Section: J2000mentioning
confidence: 99%